2006
DOI: 10.4049/jimmunol.177.11.8046
|View full text |Cite
|
Sign up to set email alerts
|

The Tumor-Promoting Effect of TNF-α Involves the Induction of Secretory Leukocyte Protease Inhibitor

Abstract: According to the cancer immunoediting concept, inflammatory mediators play not only a critical role in promoting host protection against cancer but also contribute to cancer cell growth and survival. TNF-α is a critical factor in this network. However, the mechanisms underlying the tumor-promoting effect of TNF-α have not been fully elucidated yet. We previously reported that in vitro culture of Lewis lung carcinoma 3LL cells with TNF-α-producing macrophages resulted in enhanced resistance toward TNF-α-mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 30 publications
3
14
0
Order By: Relevance
“…In this study, the SLPI-treated KB cells showed a strong increase in migration and invasion but the migration and invasion of KB cells were reduced by SLPI-siRNA, supporting the results of the in vitro wound healing assay as well as the agonistic effect of SLPI on cancer development (Devoogdt et al 2003(Devoogdt et al , 2004. Another study reported similar findings in that the down-regulation of SLPI expression reduces the capacity to form tumors in 3LL-S cells (Devoogdt et al 2006). In summary, these results showed that SLPI increases the proliferation, migration and invasion of KB cells, which suggests that SLPI is involved in the metastasis of oral carcinoma cells.…”
Section: Discussionsupporting
confidence: 86%
“…In this study, the SLPI-treated KB cells showed a strong increase in migration and invasion but the migration and invasion of KB cells were reduced by SLPI-siRNA, supporting the results of the in vitro wound healing assay as well as the agonistic effect of SLPI on cancer development (Devoogdt et al 2003(Devoogdt et al , 2004. Another study reported similar findings in that the down-regulation of SLPI expression reduces the capacity to form tumors in 3LL-S cells (Devoogdt et al 2006). In summary, these results showed that SLPI increases the proliferation, migration and invasion of KB cells, which suggests that SLPI is involved in the metastasis of oral carcinoma cells.…”
Section: Discussionsupporting
confidence: 86%
“…WFDC2 contains two WAP structural domains and belongs to the WAP protein family. Previous research indicates that proteins with a WFDC motif usually exhibit the following: A number of WAP proteins have been mapped to human chromosome 20q12-13.1, a region amplified in several types of cancers leading to the proposal that genes located on this region of chromosome 20 play a role in carcinogenesis and tumor progression (6,9); exhibit anti-inflammatory and antimicrobial activity against Gram-negative bacteria and viruses by regulating the NF-κB activity (17)(18)(19); regulate cell growth (13,14,20,21) and regulate angiogenesis and cell spread by the interference of the leucocyte cell-derived and tumor cell-derived proteinase and cytokines (8,12,22,23). Despite these findings the precise function of WFDC2 remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of SLPI was positively correlated with the increased expression of the cell cycle progression factor, cyclin D1, and its causal role in the promotion of malignant behavior was also demonstrated in lung carcinomous cells stably transfected with human SLPI-expression constructs (8,(12)(13)(14). Elafin was reported to be overexpressed in late-stage, high-grade serous ovarian carcinomas and to correlate with poor overall survival (15).…”
Section: Introductionmentioning
confidence: 99%
“…TNF-α is also known to augment its own activity by promoting the release of other soluble mediators. Devoogdt and colleagues recently showed, using gene silencing, that Secretory Leukocyte Protease Inhibitor (SLPI), induced by TNF-α in lung carcinoma cells, was involved in the tumor-promoting activity of TNF-α by an as of yet unknown mechanism [69][70][71].…”
Section: C121 Immune Effectors Can Simultaneously Sculpt Tumors Fmentioning
confidence: 99%